58 Proceedings and Acts of the General Assembly (1762-63) - (:unkn) unknown (My University, 1763)
An Act for Prohibiting All Trade with the Indians, for the Time Therein Mentioned, ch. 4, § 3: Prohibited the selling and giving to "any Indian Woman" any gunpowder or to "any Indian Man" more than one pound of gunpowder, punishable by fine.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER